PENINGKATKAN PEMAHAMAN DI KALANGAN MASYARAKAT TENTANG BAHAYA POLITIK UANG DALAM PEMILU 2024 - Sonia, Citra; Juniaro , Abil; Hazmi, Raju Moh; Ilhamsyah , Ridhwan (ASOSIASI IDEBAHASA KEPRI, 2024)
The practice of money politics by some parties has been considered normal in elections in Indonesia. The discussion of money politics has been widely discussed in the literature on voter behavior in Indonesia, both from a political, sociological, psychological, and rationale choice (political economy) perspective. There are also studies that pay attention to the influence of money politics in elections. Academic explanations of the electoral impact of money politics are also discussed in several international studies. The problem is how the solution in preventing the occurrence of money politics transactions in the election, the alternative analysis process is to use normative juridical methods with historical empirical data, through socialization, and face-to-face, participant observation and the amount of participation from the context of money politics, the role of institutions in the process of educating mass awareness through party doors and community leaders is an alternative solution to close the path of violation of election law, on the other hand public awareness and political parties and candidates are the ones who really play a role in breaking the chain of the spread of money politics transactions.